Analysis Of Factors Affecting Employment In Sidoarjo Regency - Putri Kurniawati; Ririt Iriani Sri Setiawati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Problems that occur in Indonesia that until now have not been resolved are related to labor absorption. The large number of job seekers who are not proportional to the number of available jobs makes unemployment increase. This study aims to analyze the factors that affect labor absorption in Sidoarjo Regency using three independent variables, namely economic growth, domestic investment, and district minimum wage. This research uses quantitative research methods with time series data over 15 years, starting from 2007 to 2021. The method used is multiple linear regression. The analysis tools used use IBM SPSS Statistics 25. The results showed that economic growth, domestic investment, and the district minimum wage together (simultaneously) had a significant influence on employment in Sidoarjo Regency.